2018
DOI: 10.1038/s41598-018-20197-4
|View full text |Cite
|
Sign up to set email alerts
|

Aryl hydrocarbon receptor signaling modulates antiviral immune responses: ligand metabolism rather than chemical source is the stronger predictor of outcome

Abstract: The aryl hydrocarbon receptor (AHR) offers a compelling target to modulate the immune system. AHR agonists alter adaptive immune responses, but the consequences differ across studies. We report here the comparison of four agents representing different sources of AHR ligands in mice infected with influenza A virus (IAV): TCDD, prototype exogenous AHR agonist; PCB126, pollutant with documented human exposure; ITE, novel pharmaceutical; and FICZ, degradation product of tryptophan. All four compounds diminished vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 84 publications
(127 reference statements)
2
55
0
Order By: Relevance
“…This study also showed that the AhR modulates macrophage and dendritic cell responses, including the levels of interleukin (IL)-1β, IL-10, and tumor necrosis factor (TNF)α 23. Other data show the different AhR ligands differentially modulate immunoglobulin (Ig)G and CD8+ T-cell responses to the influenza virus, with the loss of CYP1 attenuating AhR-driven effects on virusdriven immune responses 20. Whether such AhR-driven effects are regulated by variations in the mitochondrial melatonergic pathway and NAS/melatonin ratio requires investigation, including as to the relevance of these AhR-associated pathways in covid-19 infection.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…This study also showed that the AhR modulates macrophage and dendritic cell responses, including the levels of interleukin (IL)-1β, IL-10, and tumor necrosis factor (TNF)α 23. Other data show the different AhR ligands differentially modulate immunoglobulin (Ig)G and CD8+ T-cell responses to the influenza virus, with the loss of CYP1 attenuating AhR-driven effects on virusdriven immune responses 20. Whether such AhR-driven effects are regulated by variations in the mitochondrial melatonergic pathway and NAS/melatonin ratio requires investigation, including as to the relevance of these AhR-associated pathways in covid-19 infection.…”
mentioning
confidence: 63%
“…tetrachlorodibenzo-p-dioxin (TCDD), commonly found in cigarette smoke; polychlorinated biphenyl congener 126 (PCB126), a common pollutant; the novel pharmaceutical, 2-(1 0 H-indole-3 0 -carbonyl)-thiazole-4-carboxylic acid methyl ester (ITE); and the endogenous AhR ligand, 6-formylindolo[3,2-b]carbazole (FICZ), which is a tryptophan degradation product. All of these ligands can modulate immune responses to viral infection 20,21. However, it is the activation of the AhR by kynurenine and kynurenic acid that more readily links the AhR to immune inflammatory activity, as shown inFigure 1.…”
mentioning
confidence: 99%
“…Consistent with this idea, in the context of IAV infection AhR activation significantly impairs the ability of DCs to activate virus-specific CD8 + T cells via a mechanism that is in part because of to AhR-mediated events in DCs (25). This is likely not an effect that is unique to the prototype AhR agonist TCDD, as other AhR ligands cause similar changes in T cell responses to IAV infection (37). Also, soybean tar extract, which contains AhR agonists, dampened CCL17 production by mouse bone marrow-derived DCs, although it is not certain that this occurred in an AhR-dependent mechanism (86).…”
Section: Immunohorizonsmentioning
confidence: 72%
“…Dr. C. Bradfield (University of Wisconsin, Madison, WI) provided breeding stock of Ahr dbd , Ahr KO , and Ahr fx/fx mice, and colonies are continually maintained at the University of Rochester Medical Center. Vav1 cre Ahr fx/fx (Ahr DVav1 ) were created by crossing female Ahr fx/fx mice with male Vav1 cre transgenic mice (37). All mice are housed in microisolator cages in a specified pathogen?-free facility at the University of Rochester Medical Center and are provided food and water ad libitum.…”
Section: Mice and Treatmentsmentioning
confidence: 99%
“…In other mice infected with the influenza A virus, ten daily i.p. administrations of 100 lg FICZ kg À1 attenuated virus-specific immunoglobulin M (IgM) levels and elevated the proportion of Treg cells, without reducing CD8 þ T cell responses (Boule et al 2018). In other studies, treatment of mice with 2 mg FICZ (about 100 mg kg À1 ) suppressed immune responses to the influenza A, vesicular stomatitis, and Sendai viruses (Yamada et al 2016), whereas treatment of mice infected with ocular herpes simplex virus intraperitoneally with 1 mg FICZ each (about 50 mg kg À1 ) once every day for eleven consecutive days had no effect on the occurrence of ocular lesions (Veiga-Parga et al 2011).…”
Section: Differentiation Of Immune Cells and Immune Responsesmentioning
confidence: 99%